Sustainable Membrane Fabrication Using Green Chemistry Principles: A Comprehensive Review of Microwave Irradiation, Sonochemical, and Continuous Flow Methodologies - Anand Prakash (International Journal of Membranes, 2026)
Membrane-based separation technologies have emerged as indispensable tools in water purification, biomedical engineering, pharmaceutical processing, and environmental protection. However, conventional membrane fabrication processes often rely on hazardous organic solvents, energy– intensive steps, and environmentally taxing conditions. In response to increasing global emphasis on sustainability and regulatory pressures, green chemistry strategies have gained attention for enabling safer, energy-efficient, and eco-friendly membrane production. This review provides a comprehensive and structured analysis of three prominent green methodologies – microwave-assisted fabrication, sonochemical techniques, and continuous flow membrane synthesis. Each method is examined with respect to its principles, physicochemical mechanisms, operational parameters, material suitability, environmental benefits, and scalability potential. Furthermore, accompanying diagrams, tables, and mechanistic illustrations strengthen conceptual clarity. The review consolidates current advancements, research gaps, and future opportunities for integrating green chemistry principles in membrane engineering with a focus on pharmaceutical, bioprocessing, and environmental applications. By offering an in-depth understanding of sustainable membrane fabrication routes, this article aims to support researchers, industries, and academia in adopting greener technologies for next-generation membrane systems.
Keywords: Continuous flow methodology; Eco-friendly polymer processing; Energy-efficient membrane production; Microwave irradiation; Novel membrane technologies; Pharmaceutical separations; Sustainable membrane fabrication; green chemistry; sonochemical synthesis